Morphoscopy and Morphology of Pedological Coverage at the Margins of Uruguai River, West of Santa Catarina State - Bertolini, William Zanete; Costa, Isael Machado da; Lima, Gisele Leite de (Anuário do Instituto de Geociências, 2016)
Knowledge and interpretation of the sedimentary record of surface coverage and landscape soil is a valuable tool for understanding the paleoenvironment and its changes Pleistocene/Holocene why this happened during the last few thousand years of the Quaternary period. In this sense, from the pedostratigraphy and morfoestratigraphy point of view, this work intends to contribute to the understanding of the genesis of soil cover on the banks of the Uruguay River and its paleoenvironmental context that contains evidence of pre-Columbian populations along this pedogenizado stuff in Águas de Chapecó. Through morphological description and analysis morphoscopic of sands of three representative pedological profiles of low slope roofs, it is concluded that the morphoscopic analysis provided evidence of fluvial participation in both the banks of the Uruguay River where the study area is located. But the morphoscopic analysis was inefficient to distinguish the genetic origin of soil horizons in terms of allochthonous or autochthonous them.